Analisis Gaya Kepemimpinan Islami Dalam Meningkatkan Motivasi Kerja Pegawai KSPPS BMT NU Jawa Timur Cabang Lenteng Sumenep - Azzam Khalidy; Farid Ardyansyah (Pusat Riset dan Inovasi Nasional, 2023)
KSPPS BMT NU of East Java, which is a non-bank financial institution, has the task of gathering and channeling the financing, especially in Lenteng sub-district. As one of the institutions that has an important role in funding, the employees of KSPPS BMT NU East Java, Lenteng branch have duties and responsibilities, as well as the goal of each period to be able to gather or give funding to the community. Of course, it is not easy. Therefore, the leadership factor is very necessary to motivate the employees to carry out the tasks and responsibilities has been given. The purpose of this research is to analyze the styles of Islamic leadership applied and also to find out how the styles of leadership can improve the motivation of the employees of KSPP BMT NU East Java, Lenteng branch. This research used qualitative research methods. Data collection techniques used observation methods, interviews, and documentation. Based on the results of the research, the Islamic leadership style applied in KSPPS BMT NU East Java, Lenteng branch is a typology of the democratic leadership style. The style is quite good in improving the motivation of employees. It can be proved by the presence of a harmonious, open working environment as well as by giving good motivation and appreciation to the employees.